Evaluating the impact of a modified multi-modal prehabilitation program on perioperative outcomes in Chinese patients undergoing colorectal cancer surgery - Tai, Rui; Yang, Fu; Wang, Jingyi; Wan, Sibei; Xiang, Qin; Cheng, Yuhan; Fang, Fang; Sun, Jufang (Frontiers in Surgery, 2026)
AimThis study aims to evaluate the feasibility and effectiveness of a modified multi-modal prehabilitation program for Chinese patients with colorectal cancer during their preoperative hospital stay. The impact on perioperative physiological function, postoperative recovery, and overall outcomes was assessed.DesignA prospective, randomized controlled trial.MethodsA prospective, randomized controlled trial was conducted with 200 patients (100 experimental, 100 control) at a tertiary hospital in Shanghai. The experimental group received a modified multi-modal prehabilitation program, including inspiratory muscle training, aerobic exercise, nutritional supplementation, and psychological support, while the control group received standard perioperative care. Primary outcomes were assessed using the 6-Minute Walk Test (6MWT) on the day before surgery and 30 days postoperatively. Secondary outcomes included postoperative hospital stay duration, time to first flatus, ambulation, oral intake, and incidence of postoperative complications.ResultsThe experimental group showed significantly greater improvements in 6MWT performance compared to the control group both before surgery (400.40 m vs. 383.25 m, P < 0.01) and 30 days postoperatively (375.40 m vs. 336.85 m, P = 0.03). Additionally, the experimental group had a shorter postoperative hospital stay (7.91 days vs. 9.06 days, P < 0.01) and earlier recovery milestones (P ≤ 0.01) compared to the control group. The incidence of postoperative complications was slightly lower in the experimental group, though not statistically significant.Clinical Trial Registrationhttps://www.chictr.org.cn/, Identifier ChiCTR2200055764.